Personalized therapy in breast cancer - Marmé, Frederik; Schneeweiss, Andreas (Onkologie, 2012)
Systemic treatment of non-metastatic breast cancer is based on endocrine therapy, cytotoxic chemotherapy, and molecular targeted therapy - with the major problems of immense overtreatment of patients who would not relapse without systemic therapy and the failure of treatment in others whose disease still recurs. These deficits can only be overcome by the identification of new and better prognostic and predictive markers. Currently, adjuvant treatment stratification is based on a limited number of established factors, namely locoregional tumour stage, age, grade, expression of hormone receptors, HER2, and Ki-67. Molecular profiling techniques, however, have revolutionized our understanding of breast cancer as a heterogeneous disease. Future results from even more comprehensive genetic analyses as part of the coordinated cancer genome projects will help to develop better treatment stratifications and new therapeutic approaches. Efforts to realize the dream of a personalized treatment for breast cancer will include drug development and intelligent design of trials for increasingly small subgroups of patients with specific host and disease characteristics. This will only be made possible by a strong cooperation between basic researchers and translational scientists, clinicians, as well as academia and industry.